'It was, perhaps, the most important one' students' perceptions of national tests in terms of test-taking motivation. Issue 2 (4th March 2019) - Knekta, Eva; Sundström, Anna
Abstract: The aim of this study was to examine ninth-grade students' perception of a Swedish national test in science (high-stakes for the students) and a field trial (low-stakes for the students), in terms of test-taking motivation. The study is based on semi-structured interviews with 12 students. Overall, the students had a positive perception of the national test; they were motivated to do their best, believed they did well and found the test important and good. Several students were nervous before the test and some during the test whereas others felt okay, or even enjoyed taking the national test. The students talked about less effort and test anxiety in the field trial and perceived the test as less important compared to the national test. The interviews provided a rich understanding of the different aspects of test-taking motivation as described by the expectancy-value theory. Furthermore, they indicated how the test administration could be adjusted so as to achieve higher test validity.